2009
DOI: 10.1002/lt.21785
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation at the extremes of the body mass index

Abstract: Controversies exist regarding the morbidity and mortality of patients undergoing liver transplantation at the extremes of the body mass index (BMI ; severely obese, 35 to Ͻ40 kg/m 2 ; and very severely obese, Ն40 kg/m 2 . Survival rates were compared among these 6 categories via Kaplan-Meier survival curves with the log-rank test. The underweight and very severely obese groups had significantly lower survival. There were 1827 patients in the underweight group, 1447 patients in the very severely obese group, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
153
1
19

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(179 citation statements)
references
References 28 publications
6
153
1
19
Order By: Relevance
“…4,5 Notably, the latter aspect could have been responsible of the difference between our findings and the results reported by previous meta-analyses as concerns the mortality risk. In fact, we found a pretty robust increase in OR at 30 days, when either BMI ≥30 and 40 were evaluated (1.90; CI: 1.38, R E F E R E N C E S 1 and prevention of relapse following surgery in Crohn's disease, 2 although its efficacy in the induction and maintenance of remission in Crohn's disease remains disputed.…”
contrasting
confidence: 97%
See 1 more Smart Citation
“…4,5 Notably, the latter aspect could have been responsible of the difference between our findings and the results reported by previous meta-analyses as concerns the mortality risk. In fact, we found a pretty robust increase in OR at 30 days, when either BMI ≥30 and 40 were evaluated (1.90; CI: 1.38, R E F E R E N C E S 1 and prevention of relapse following surgery in Crohn's disease, 2 although its efficacy in the induction and maintenance of remission in Crohn's disease remains disputed.…”
contrasting
confidence: 97%
“…3 In addition, the drug may be of benefit in a subset of patients with irritable bowel syndrome. 4,5 Diverticular disease is a chronic disorder of the lower GI tract.…”
mentioning
confidence: 99%
“…Similarly to previous studies, we found that a low BMI was independently associated with mortality after liver transplantation. 20 We also found that only male patients with extreme sarcopenia (ie, those in the lowest L3 SMI sextile) had worse outcomes after liver transplantation; however, the presence of sarcopenia was associated with a longer recovery period after transplantation, which was reflected by the longer hospital stay needed because these patients required more inpatient rehabilitation. Also, similarly to previous studies, 4 we found that sarcopenia was associated with higher rates of bacterial infections, which were related to links between malnutrition and/or sarcopenia and impaired immunity.…”
Section: Discussionmentioning
confidence: 59%
“…We normally used nasogastric or nasoenteral feeding only for those patients with a body mass index less than 18.5 kg/m 2 because this has been shown to be a risk factor for mortality after liver transplantation, 4 but none of the patients in this cohort had a body mass index below this threshold.…”
mentioning
confidence: 99%